Market regulation between economic and ecological values: Regulatory authorities and dilemmas of responsiveness. (July 2021) - Besselink, Tobias; Yesilkagit, Kutsal
The regulation of markets emerged as one of the core pillars of government policies during the 1990s. However, the ascendance of ecological values and issues, such as sustainability and security in the following decades challenge some of the basic tenets of the underlying neo-liberal ideas. We argue in this paper that market and competition regulators have come under pressures to uphold the market and economic values of the prevailing anti-trust policies while being responsive to societal pressures that cherish non-economic values. Competition authorities find themselves locked-in to economic theories of regulation and find little room for engaging with ecological issues. We illustrate this with the case of the Dutch competition authority's approach to managing the balance between economic and sustainability and animal welfare values.